The good life: A comparative analysis of the evolution of good life´s basic goods between the Scandinavian countries and Southern European countries - Pedro, Nádia do Carmo (2022)
This work is a comparative analysis and investigation of the evolution of the so-called basic goods, which correspond to the following elements: Health, Security, Respect, Personality, Friendship, Harmony with Nature and Leisure, between the Scandinavian countries and Southern European countries. These seven elements are identified by the Skidelskys' as being the foundations of the good life. This study does a reflection on the concept of good life and the way in which we try to fit it, as well as happiness, in analyzes of quality of life and human development. This work appears as a criticism of the use of studies based on the use of happiness to measure human development due to its subjective character. Thus, this thesis proposes the methodology used by Skidelsky's in their book How Much Is Enough (2012) to measure, compare and analyze the evolution of the basic goods between these two groups of countries between the years of 2008, when the financial crisis arise, and 2020, the year of the pandemic, as a way of analyzing human development. Each element is analyzed based on social and socio-economic indicators through a descriptive analysis. The premise followed by this thesis is that the greater the positive evolution of basic goods, the closer a country is to achieving the good life or the means to achieve the good life.